Compassionate Knowing: Building a Concept Grounded in Watson's Theory of Caring Science. (July 2019) - Constantinides, Shannon M.
Compassionate knowing is the practice of intentional presence to relieve suffering. Inspired by Carper's patterns of knowing, it is an additional form of knowing grounded in caring science. Likewise, the concept of compassionate knowing is framed by tenets of Buddhist philosophy and George's emancipatory theory of compassion. Intentional presence is defined as a conscious and altruistic choice, born of moral virtue and selflessness, to act in a thoughtful, empathetic, and humanistic way that honors and gives meaning to the uniqueness of each patient and caring-healing nurse-client interaction. Relieving suffering is defined as the nurse responding to the needs of the patient with loving-kindness to alleviate a perceived or real threat to self-integrity.